Belowground stressors and long-term seagrass declines in a historically degraded seagrass ecosystem after improved water quality. Issue 1 (December 2017) - Fraser, Matthew; Kendrick, Gary
Abstract Continued seagrass declines in ecosystems with improved water quality may be driven by sediment stressors. One of the most cited examples of a seagrass ecosystem with declines is Cockburn Sound, Western Australia, where 75% of seagrasses (2169 ha) were lost in the 1960s–1980s due to poor water quality. Water quality has subsequently improved in Cockburn Sound, yet shoot density declines continue in some areas. Here, we investigated if sediment stressors (sulfide intrusion and heavy metals) contributed to decliningPosidonia sinuosa shoot densities in Cockburn Sound. Seagrass δ34 S were depleted at sites with a history of seagrass declines, indicating seagrasses at these sites were under sulfide stress. Heavy metals (Fe, Zn, Mn, Cr, Cu and Cd) in sediments and seagrasses did not show clear patterns with shoot density or biomass, and largely decreased from similar measurements in the late 1970s. However, seagrass cadmium concentrations were negatively correlated to seagrass biomass and shoot density. High cadmium concentrations interfere with sulfur metabolism in terrestrial plants, but impacts on seagrasses remain to be explored. Given that sulfide intrusion can prevent recolonization and drive seagrass declines, management plans in degraded seagrass ecosystems should include management of sediment stressors and water quality to provide comprehensive management.